Gambaran Health Seeking Behaviour pada Remaja dalam Upaya Meningkatkan Kesehatan Reproduksi - Putri, Wendy Dias Krisna; Astutik, Heny; Suharno, Budi (FORIKES, 2022)
Adolescents have a tendency to engage in risky behavior that increases morbidity and mortality. The purpose of this study is to describe health seeking behavior in adolescents in an effort to improve reproductive health. This research was an explanatory descriptive study with a survey approach. The research subjects were 60 adolescents who were selected by purposive sampling technique. Data were collected through filling out a questionnaire and then analyzed descriptively. Based on the results of the study, it was known that most adolescents had a high level of trust in health services, had a high level of support system, and had a high level of need for health services. Most adolescents had good health seeking behavior. It is hoped that adolescents can improve their health seeking behavior and choose the right information related to reproductive health.Keywords: adolescents; reproduction health; health seeking behaviorABSTRAK Remaja memiliki kecenderungan untuk melakukan perilaku berisiko yang meningkatkan angka kesakitan dan kematian. Tujuan dari penelitian ini adalah untuk menggambarkan health seeking behavior pada remaja dalam upaya meningkatkan kesehatan reproduksi. Penelitian ini merupakan penelitian deskriptif eksplanatif dengan pendekatan survei. Subyek penelitian adalah 60 remaja yang dipilih dengan teknik purposive sampling. Data dikumpulkan melalui pengisian kuesioner lalu dianalisis secara deskriptif. Berdasarkan hasil penelitian diketahui bahwa sebagian besar remaja memiliki tingkat kepercayaan yang tinggi terhadap layanan kesehatan, memiliki tingkat support system yang tinggi, dan memiliki tingkat kebutuhan yang tinggi terhadap layanan kesehatan. Sebagian besar remaja memiliki health seeking behavior yang baik. Diharapkan remaja dapat meningkatkan health seeking behavior dan memilih informasi yang tepat terkait dengan kesehatan reproduksi.Kata kunci: remaja; kesehatan reproduksi; health seeking behavior